Arabic Learning Model Development In Improving Reading Skill - Isop Syafe’i,; Dadan F Ramdhan (State Institute of Islamic Studies (IAIN) Salatiga, 2018)
Arabic course is a university course that must be followed by all students of UIN Sunan Gunung Djati. Based on the observation, learning Arabic in UIN Sunan Gunung Djati Bandung reap the constraints and challenges in its implementation. To overcome this problem, the development of learning model can be considered as an alternative. This research uses research and development (R D) method. Located on UIN Sunan Gunung Djati Bandung campus in Psychology course. Research subjects in this study were students and lecturers of Islamic Education Department Faculty of Tarbiyah and Teacher Training UIN Sunan Gunung Djati Bandung. In the implementation, this learning model is quite effective in order to improve the performance of lecturers and student motivation in the process of learning Arabic and is known to be more effective when compared with the Arabic learning that has been going on.